The Climate Changes Awareness Among Science and Social Sciences Student Teachers at Sultan Qaboos University - l-Shuaili, Ali; Al-Rabaani, Ahmed (Jordan Journal of Educational Sciences, 2010)
The study aims at finding out the extent of Sultan Qaboos University student teachers’ awareness of climatic changes from the perspective of the students themselves. The study sample consisted of 127 male and female Science and Social Sciences student teachers, who enrolled in their final year at the College of Education in the year 2008/2009. A 69-item questionnaire had been developed by the researchers covering the following domains: cognitive, affective and psychomotor components. The instrument validity was verified by a panel of judges, whereas the reliability Cronbach alpha coefficient of internal consistency was (0.822). The findings revealed that there were significant differences in students teachers’ cognitive domain awareness with respect to gender in favor of female students, and in the affective domain with respect to major in favor of social sciences specialization. The results also showed no significant differences(α = 0.05)both in affective and psychomotor domains with respect to gender and in cognitive and psychomotor domains with respect to major. Accordingly, the researchers suggest further studies and recommend enhancing student teachers’ knowledge of social, economical and political impacts of climate changes.(